In Silico Screening of Schleichera oleosa Phytocompounds as Estrogen Receptors Alpha Inhibitors for Breast Cancer - Pratiwi, Radita Intan Aisyah; Rahayu, Tintrim; Mubarakati, Nurul Jadid (JSMARTech, 2020)
Abstrak: This study aimed to predict the potential activity, toxicity, and interaction of fifteen bioactive compounds from Schleichera oleosa as estrogen receptors alpha inhibitors via in silico analysis. Active compound was downloaded from the PubChem database, and the 3D structure of the human estrogen receptor alpha (ERÎ±) was obtained from the Protein Data Bank database with 4-Hydroxytamoxyfen as a positive control. The interaction of bioactive compounds with macromolecule was examined via a molecular specific docking using AutoDock Vina with PyRx 9.5 software. The protein was visualized using Discovery Studio 4.1. The drug-likeness property and human intestinal absorption of those fifteen bioactive compounds were evaluated through absorption, distribution, metabolism, and excretion (ADME) analysis using the pkCSM online tool program. The interactions between proteins and ligands are largely through the formation of hydrogen and van der Waals bonds. The binding energy of lupeol acetate, lupeol, schleicheol 1, betulinic acid, betulin, beta-sitosterol, schleicherastatin 7, schleicherastatin 2, schleicherastatin 4, scopoletin, schleicherastatin 3, schleicherastatin 1, schleicherastatin 6, schleicherastatin 5 alpha and schleicherastatin receptors including -8.3, -8.3, -7.1, -7.1, -6.7, -6.6, -6.6, -6.5, -6.5, -6.3, -6.2, -6.2 -6.1, -5.9 and -5.5 kcal / mol, respectively . The in silico ADME analysis also revealed that lupeol and lupeol acetate were the best active compound that passes the test based on the Lipinski rule, ADME, and toxicity. Therefore, it can be stated that Schleichera oleosa has potential as an inhibitor of alpha estrogen receptors. The inhibitory activity of alpha estrogen receptors has led to new breakthroughs in plant-based medicinal products, particularly for breast cancer.Â Keyword: Schleichera oleosa, alpha estrogen receptors, phytocompound, breast cancer and in silico